Clinical and Neuroimaging Characteristics of Pediatric Acute Disseminating Encephalomyelitis With and Without Antibodies to Myelin Oligodendrocyte Glycoprotein - Zhang, Min; Shen, Jin; Zhou, Shuizhen; Du, Xiaonan; Li, Wenhui; Yu, Lifei; Zhang, Yunjian; Wang, Yi; Zhang, Linmei (Frontiers in Neurology, 2020)
Objective: To compare the clinical and neuroimaging characteristics of anti-myelin oligodendrocyte glycoprotein antibody (MOG-ab) negative and positive pediatric acute disseminating encephalomyelitis (ADEM) patients. Methods: Clinical characteristics, neuroimaging features, ancillary examination results and outcomes of pediatric ADEM patients were retrospectively reviewed between February 2016 and July 2019. Results: Among 37 pediatric ADEM patients, 24patients, (11girls and 13 boys) fulfilled the inclusion criteria. The median age was 72 (range 19–156) months and the median follow-up duration was 20 (range 12–48) months. Children with ADEM and MOG-abs presented with increased ataxia, reduced bladder/rectum dysfunction, and paralysis compared to children without MOG-abs. An important finding was that no significant differences existed in age at symptom onset, sex ratio, time from immunotherapy to clinical improvement and clinical recovery, or modified Rankin Scale (mRS) at the last follow-up. More typical cerebral MRI lesions were detected in patients with ADEM and MOG-abs than in children without MOG-abs (11/12[91.7%] vs. 8/12[66.7%]). Cerebellar lesions were higher in ADEM patients with MOG-abs (7/12, 58.3%) than in without MOG-abs (2/12, 16.7%). While seven children had abnormal spinal MRI findings (7/12, 58.3%) and 5 had longitudinally extensive transverse myelitis (LETM) (5/12, 41.7%) per group, the coexistence of spinal dysfunction and abnormal spinal MRI was lower in ADEM with MOG-abs (2/12, 16.7%) than in children without MOG-abs (7/12, 58.3%). Clinical improvement was achieved 1 week after immunotherapy. Most children in both groups achieved clinical recovery within 3 months after immunotherapy, although two (16.7%) patients with ADEM and MOG-abs had persistent neurological sequelae at the last follow-up. Conclusion: MOG-abs-positive ADEM is a major subtype of pediatric ADEM. Ataxia is the most common clinical presentation in pediatric ADEM and MOG-abs. Children with ADEM and MOG-abs have similar patterns of lesions, characterized by large, bilateral, widespread lesions as well as more cerebellar lesions than children without MOG-abs. Most spinal lesions were subclinical in pediatric ADEM with MOG-abs. A favorable prognosis can be achieved for pediatric ADEM regardless of the MOG-abs status. However, some patients with MOG-abs are likely to have more severe neurological sequelae.